2016
DOI: 10.1161/strokeaha.116.013281
|View full text |Cite
|
Sign up to set email alerts
|

Constraint-Induced Movement Therapy for Upper Extremities in People With Stroke

Abstract: Figure.Effect of constraint-induced movement therapy and its modified forms (constraint) versus other rehabilitative techniques or none (control). SMD indicates standardized mean difference.by guest on May 12, 2018

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 1 publication
3
47
0
5
Order By: Relevance
“…Consistent with previous studies, significant differences were found in most of the subscales in the ARAT and FMA between the SR-mCIMT or mCIMT with the control groups [1]. The combination of SR with mCIMT was found to enhance patients' arm function specifically in coordination, daily task performance and self-perceived amount of arm use in functional tasks after the intervention better than the mCIMT alone group.…”
Section: Discussionsupporting
confidence: 88%
“…Consistent with previous studies, significant differences were found in most of the subscales in the ARAT and FMA between the SR-mCIMT or mCIMT with the control groups [1]. The combination of SR with mCIMT was found to enhance patients' arm function specifically in coordination, daily task performance and self-perceived amount of arm use in functional tasks after the intervention better than the mCIMT alone group.…”
Section: Discussionsupporting
confidence: 88%
“…Spinal reflex activity plays an important role in the proper functioning of mechanisms related to tonus control and postural adjustments during movement [1]. Previous studies including injured individuals have tested therapeutic strategies, such as drug and unspecific motor interventions, intended to increase spinal inhibitory control for post-stroke spasticity [2,3]. However, systematic reviews have shown that motor [2,3] and pharmacological [4,5] approaches have limited effect, and result in a risk of adverse events.…”
Section: Introductionmentioning
confidence: 99%
“…The CIMT protocol was informed by published research (Corbetta et al, ; Taub et al, ) and knowledge acquired from experienced Canadian and Australian therapists (TS and PF, respectively). Components included (a) intensive training of the more‐affected arm for 10 weekdays, with 1:1 supervision and shaping of targeted motor behaviours, and recording of daily repetitions; (b) a transfer package of behavioural techniques to transfer gains made outside supervised CIMT sessions, including a signed behavioural contract, 10 daily homework assignments, a homework diary, administration of 10 questions from the MAL each morning; and (c) use of a mitt restraint for 90% of waking hours worn on the less affected arm.…”
Section: Methodsmentioning
confidence: 99%
“…International guidelines (Hebert et al, ; Royal College of Physicians, ; Stroke Foundation, ) recommend CIMT for stroke survivors with active finger and wrist extension, because CIMT improves upper limb function. A Cochrane systematic review, including 42 trials demonstrated small but consistent improvements in upper limb function following two or three weeks of intensive CIMT (Corbetta, Sirtori, Castellini, Moja, & Gatti, ). Of the 42 trials, 79% ( n = 24) involved outpatients, 26% ( n = 11) involved inpatients and 17% ( n = 7) involved a mixed population, with improved outcomes early (zero to 3 months) and later (>9 months) post‐stroke.…”
Section: Introductionmentioning
confidence: 99%